The social and environmental impacts of biofuel feedstock cultivation: Evidence from multi-site research in the forest frontier - German, L.; Schoneveld, George C.; Pacheco, P. (2011)
Preoccupation with global energy supplies and climate change in the global North, and a desire to improve the balance of trade and capture value in the emerging carbon market by developing countries, together place biofuels firmly on the map of global land use change. Much of this recent land use change is occurring in developing countries where large agro-ecologically suitable tracts of land may be accessed at lower economic and opportunity cost. This is leading to the gradual penetration of commercial crops that provide suitable biofuel feedstocks (e.g., sugarcane, soybean, oil palm, jatropha) into rural communities and forested landscapes throughout many areas of the global South. Expansion of biofuel feedstock cultivation in developing countries is widely embraced by producer country governments as a means to achieve energy security and stimulate rural economic development through employment and smallholder market integration. It is also expected that foreign and domestic investments in biofuel feedstock cultivation will lead to positive economic spillovers from knowledge transfer and investor contributions to social and physical infrastructure. While biofuel feedstocks are expanding through large industrial-scale plantations and smallholder production alike, the expansion of industrial-scale production systems has been countered by a critical response by civil society actors concerned about the implications for rural livelihoods, customary land rights, and the environmental effects of biofuel feedstock cultivation. To date, however, limited data exist to demonstrate the conditions under which widely anticipated economic and climate change mitigation benefits accrue in practice, and the implications of these developments for forests, local livelihoods, and the climate change mitigation potential of biofuels. In such a situation, debates are easily polarized into those for and against biofuels. This special issue seeks to nuance this debate by shedding light on the local social and environmental impacts accruing to date from the expansion of biofuel feedstock cultivation through in-depth case studies in 6 countries in Asia, Africa, and Latin America. Findings provide a more nuanced picture of costs and benefits, and point to a host of risks that need to be proactively managed to leverage the potential of the industry as an engine of national social and economic development.